2011
DOI: 10.1007/s00335-011-9342-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants for intramuscular fat content and water-holding capacity in mice selected for high muscle mass

Abstract: Intramuscular fat content and water-holding capacity are important traits in livestock as they influence meat quality, nutritive value of the muscle, and animal health. As a model for livestock, two inbred lines of the Berlin Muscle Mouse population, which had been long-term selected for high muscle mass, were used to identify genomic regions affecting intramuscular fat content and water-holding capacity. The intramuscular fat content of the Musculus longissimus was on average 1.4 times higher in BMMI806 than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 63 publications
1
15
0
4
Order By: Relevance
“…The most significant SNP in this region was an intronic SNP within PDE1A. The PDE1A gene is involved in a pathway related to myofibroblast formation in smooth muscle in humans [55] while previous genome-wide studies in mice have identified the PPP1R1C gene as a possible candidate gene for muscle mass [56]. Overall, the allele frequencies of the favorable alleles in this 1-Mb region were similar in all five breeds, which support a breed-specific association with DHQ, DIT, TW, and WOW in LM rather than an imputation error.…”
Section: Other Candidate Genesmentioning
confidence: 98%
“…The most significant SNP in this region was an intronic SNP within PDE1A. The PDE1A gene is involved in a pathway related to myofibroblast formation in smooth muscle in humans [55] while previous genome-wide studies in mice have identified the PPP1R1C gene as a possible candidate gene for muscle mass [56]. Overall, the allele frequencies of the favorable alleles in this 1-Mb region were similar in all five breeds, which support a breed-specific association with DHQ, DIT, TW, and WOW in LM rather than an imputation error.…”
Section: Other Candidate Genesmentioning
confidence: 98%
“…The selection history of BMM has been described previously [28]. We used the BMMI806 and BMMI816 lines, which are hyper-muscular but do not carry the Mstn Cmptdl1Abc mutation.…”
Section: Methodsmentioning
confidence: 99%
“…Genome scans have identified a large number of QTL affecting these traits in pigs. Accordingly, genes, which encode key enzymes or key regulators in lipid and energy metabolism located within relevant QTL regions, are logical choices in the candidate gene analysis for these traits (Chadt et al 2008;Lin 2009;Kärst et al 2011).…”
Section: Intramuscular Fat (Imf)mentioning
confidence: 99%